Detachment in conventional and advanced double-null plasmas in TCV. (18th October 2021) - Février, O.; Theiler, C.; Coda, S.; Colandrea, C.; de Oliveira, H.; Duval, B.P.; Gorno, S.; Labit, B.; Linehan, B.; Maurizio, R.; Perek, A.; Reimerdes, H.; et al.
Abstract: Divertor detachment is investigated on the Tokamak à Configuration Variable (TCV) for conventional and alternative double-null (DN) magnetic geometries in L-mode, Ohmic density ramps and then compared to precisely matched single-null (SN) geometries. The poloidal flux expansion at the outer strikepoint(s) is varied by a factor 2 and the total flux expansion by 30% in lower single null (LSN) and DN configurations. Leg power sharing for DN and near-DN in attached conditions is in line with previous studies in other devices, with balanced power partition between upper and lower divertor achieved for | δR sep | ≲ λ q /2. This results in a reduction in the lower outer target integral and peak heat flux compared to a LSN by 30%. Unlike previous studies, λ q is fairly insensitive to δR sep . The detachment threshold in these geometries is investigated from target measurements with wall-embedded Langmuir probes and two-dimensional CIII line emissivity profiles across the two divertor regions. DN plasmas display clear benefits compared to their LSN counterparts. Transitioning from a LSN to DN shows a substantial reduction, of approx. 20%–25%, in the detachment threshold for the active divertor legs as well as a 50% higher radiated fraction at all n e . The density limit is simultaneously reduced in DN by 10%–20%. Across the explored range, poloidal flux expansion has only a small effect on the detachment threshold in LSN (as seen in previous experiments), and no effect in DN, with similar observations for the total flux expansion. In general, no strong benefits of increased poloidal or total flux expansion are observed across the explored range.